Perspectives, Challenges, and Achievements of Multiple Sclerosis Patients in a Technology-Assisted Physical Activity Program - Rodríguez, Sebastián (2026)
Introduction: At the National University Hospital in Introduction: At the National University Hospital in Bogotá, Colombia, there was a recognized need to promote physical activity among patients with multiple sclerosis due to their low participation rates and the lack of suitable spaces. To address this issue, the "Less Sclerosis, More Movement" project was designed in collaboration with the patients. Objective: The aim was to systematize the management, design, and execution of the "Less Sclerosis, More Movement" project, as well as to explore patients' perspectives on participation barriers, their preferences, expectations before the project, and achievements and challenges after participating. Methodology: The project was promoted through social media, medical appointments, and a YouTube live session. Discussions were held with interested parties to identify access barriers, preferences, and expectations. The FANTASTICO and IPAQ questionnaires were administered, and patients were asked to create body maps for a community diagnosis. Based on the collected data, a technology-mediated physical activity program was designed with a strong educational component to encourage active lifestyles and reduce sedentary behavior. Results: Identified barriers included inadequate urban infrastructure, deficiencies in transportation, and high costs and travel times. Patients preferred exercises that required minimal equipment, were progressive and moderate, and offered support and motivation, safety, and a variety of options. Body maps revealed that the upper limbs had greater movement potential, while the lower limbs and lumbar region experienced more difficulties and pain. Patients increased their physical activity, reduced sedentary behavior, gained knowledge about physical activity, overcame the fear of falling, and became empowered in their health, feeling part of a supportive community. Conclusions: The "Less Sclerosis, More Movement" project proved to be a viable alternative for improving the lifestyles of patients with multiple sclerosis at the National University Hospital, offering a solution for engaging in physical activity despite environmental barriers.